RENDERING VERBAL IRONY OF “ONE FLEW OVER THE CUCKOO’S NEST”: NOVEL, CINEMATIC ADAPTATION AND LITHUANIAN SUBTITLES (Journal of Contemporary Philology, 2023)
This article analyses the transformation of verbal irony within literary works during adaptation and subtitle translation processes. During the process of adaptation, verbal irony is often altered or lost. In the realms of Lithuanian cinema, subtitling is a common mode of presentation, necessitating additional adjustments to accommodate translation constraints. The study is structured into theoretical and empirical parts. Firstly, it delves into irony typology, characteristics, adaptation strategies, and subtitling approaches. Then, it employs a comparative methodology to analyse verbal irony in Ken Kesey's novel "One Flew Over the Cuckoo's Nest" (1962), its cinematic adaptation by Miloš Forman (1975), and the Lithuanian subtitle translation by Narius Kairys (2018). This method unveils how verbal irony can change or persist during adaptation and subtitling processes. The examples analysed illustrate that the verbal irony from the novel may be lost or simplified and shortened in the adaptation, but it may also be complemented by non-verbal elements, such as acting and intonation. This research revealed that the film contains new cases of verbal irony absent from the original literary work. Notably, the verbal irony in the subtitles is simplified by using a near-synonym expression, omission or changes in word class and, consequently, loses its original impact.
Keywords: verbal irony; abridgement; subtitling constraint; audiovisual translation